Lipomatous hypertrophy of the interatrial septum in a child with atrial tachycardia. Issue 6 (June 2016) - Tutar, Ercan; Çiftçi, Ömer; Fitoz, Suat; Kendirli, Tanıl; Ödek, Çağlar; Uçar, Tayfun; Kansu, Aydan
Abstract: A 13‐year‐old girl who had been on home parenteral nutrition for 6 months has been presented with multifocal atrial tachycardia and atrial fibrillation. Echocardiography and multislice computed tomography showed fat accumulation on the interatrial septum. Lipomatous hypertrophy of the interatrial septum has never been reported in children.